Caracterização Química do Óleo Essencial de Philodendron sp. no Município de São João da Baliza, Roraima - Bacchus, Nakita Eugene; de Oliveira, Wélida do Nascimento; Marangon, Cristiane; de Moraes, Cléria Mendonça (Orbital: The Electronic Journal of Chemistry, 2015)
In the Amazon region of Brazil, the roots of different species of Philodendron sp. are used in traditional medicine. This study aims to characterize the chemical composition of the essential oils of Philodendron genus, native in mountain area in the municipality of São João da Baliza, from the Roraima state. The essential oils roots were extracted by hydrodistillation in Clevenger type apparatus for a period of three consecutive hours. The identification of chemical constituents was made by comparison of the mass spectra of the substances with the database of the GCMS system and Kovats index.DOI: http://dx.doi.org/10.17807/orbital.v7i4.774